If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 9 + -6x Solving 15 = 9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 15 + 6x = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 15 + 6x = 9 + 0 15 + 6x = 9 Add '-15' to each side of the equation. 15 + -15 + 6x = 9 + -15 Combine like terms: 15 + -15 = 0 0 + 6x = 9 + -15 6x = 9 + -15 Combine like terms: 9 + -15 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| (4y)+(3y)=180 | | .5x=1.45 | | (3x-18)+(2x+12)=180 | | 2(2)+4=2x | | 3a-3(7+5a)=9(2+a) | | (4y)+(3x-18)+(3z)+(2x+12)=360 | | 2(2)+4=x | | 12x-25=6x+15 | | (19x-17)-(3x-72)= | | 8(120)=x | | 8(15)=y | | 7+2t-4=8t+11-5t | | 2x-15=5x | | 6x+2=4x+12 | | 4x+63=14x-7 | | -3(x+5)=-27 | | 9x+17=5x+13 | | 6(2x+3)=66 | | 3(m-4)+2(5+2m)=29 | | 5+7y=2x+7+6y | | 16x+12=8x+41 | | 6x=3x+3 | | 9x+6=-57 | | r^3-3r+2=0 | | y=3(1)-10 | | 3x-10=2x-5 | | P(x)=x^3+7x^2+4x | | m^6-16m^3+64=0 | | 6x+3=6(4)+3 | | .50(6-y)=y | | -10.2x=71.4 | | 4x^2-33x+41=-9x+6 |